VENTlLASI ALAMIAH PADA RUMAH KACA STANDARD PEAK TIPE CURAM TERMODIFtKASI - Herry Suhardiyanto; Yudi Chadirin; Sumini .; Titin Nuryawati (Jurnal Keteknikan Pertanian, 2007)
ABSTRACT During the daytime in the tropical region, air temperature inside the greenhouse rises some degrees above the temperature level of outside air. Many greenhouses are build very tight. It formed hot air pocket in upper part of the greenhouse. A modification should be done to allow maximum air exchange rate through natural ventilation. This paper deals with the evaluation of natural ventilation role in reducing air temperature in the modified greenhouse as compared to that in the existing greenhouse. Results showed thal greenhouse modification by increasing the area of side wall openings added 11.82 % air flow rate and reduced the temperature of the inside air about 1°C to 3 °C. The calculated air exchange In both greenhouses agreed well with the measured values. Keywords: greenhouse in the tropics, neutral pressure level, air exchange rate. Diterima: 29 Juni 2007; Disetujui: 19 Agustus 2007